Synthesis, modification, characterization and biological activity of 3-hydroxybenzaldehydesalicylhydrazide [Sintesis, modifikasi, pencirian dan aktiviti biologi 3-hidroksibenzaldehidesalisilhidrazida] - Nornadia, Jasin; Meng, Guan Tay; Hashimatul Fatma, Hashim (Malaysian Society of Analytical Sciences, 2017)
A series of hydrazone Schiff base (compounds S, S8, S10 and S12) were synthesized by condensation reaction of salicylhydrazide with 3-hydroxybenzaldehyde, 3-(octyloxy)benzaldehyde, 3-(decyloxy)benzaldehyde and 3-(dodecyloxy) benzaldehyde, respectively. Herein, the addition of alkane numbers are reported using suscessful Williamson etherification method by reacting 3-hydroxybenzaldehyde with bromooctane, bromodecane and bromododecane, respectively. All compounds were characterised using Fourier Transform Infrared and 1H Nuclear Mangnetic Resonance spectroscopic. The compounds were assayed to antibacterial activity against Gram-positive and Gram-negative bacteria using Bacillus cereus and Escherichia coli by disc diffusion method. Interestingly, among the compounds tested S8 showed a strong inhibition against Escherichia coli and none of the compounds tested show significant result against Bacillus cereus.